Immediate and Subsequent Effects of Response Interruption and Redirection on Targeted and Untargeted Forms of Stereotypy. (July 2013) - Pastrana, Sarah J.; Rapp, John T.; Frewing, Tyla M.
A number of studies have shown that response interruption and redirection (RIRD) decreases immediate engagement in targeted stereotypic behaviors; however, its effects on untargeted stereotypy have not yet been studied, and its effects following removal of treatment are unclear. We evaluated the immediate and subsequent effects of RIRD on targeted motor stereotypy, as well as untargeted but higher probability vocal stereotypy, of two participants diagnosed with autism, using a three-component multiple-schedule design. Treatment with RIRD decreased immediate engagement in motor stereotypy for both participants, and did not increase subsequent engagement above baseline levels for either participant. In addition, RIRD produced modest changes in immediate engagement in untargeted vocal stereotypy for both participants. We briefly discuss the clinical implications and limitations of the findings from this study.